"Feedback is indeed a dainty dish to set before the Trust": Comparing how online patient feedback is responded to and used across three hospital Trusts in England - Lauren Ramsey; Laura Sheard; Rebecca Lawton; Jane O'Hara (The Beryl Institute, 2023)
Patients are increasingly reporting about their healthcare experiences in an unsolicited manner online. This emerging resource may offer valuable opportunities for organisational learning. Our study aimed to compare how online patient feedback was responded to and used for improvement in three hospital Trusts. Ethnographic data were collected across three hospital Trusts in England, recruited according to the way they responded to online patient feedback. Findings from three case studies were brought together using a reflexive thematic analysis approach, via a multi-case analysis. Three key themes were highlighted. Firstly, the organisational rationale for engaging with patient feedback influenced levels of compassion felt for feedback providers, and in turn, the extent feedback was valued and learned from. Secondly, multidisciplinary collaboration between patient experience teams and the wider organisation helped to disseminate ownership felt for feedback and overcome 'contextual blindness'. Thirdly, the risk of patient feedback falling into an 'abyss' was reduced when staff prioritised learning over and above collecting and reporting data, and when managers disseminated a passion for improvement. Overall, online feedback was considered a courageous step into the unknown. However, these barriers could be culturally overcome. Our multi-case analysis demonstrates that there is still a way to go for some organisations to culturally embrace online patient feedback as a valued means to improve. However, we present five key suggestions to inform policy and practice and support the use and usefulness of online patient feedback for organisational learning. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.